2005
DOI: 10.1093/rheumatology/keh571
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the long-term efficacy of local methyl prednisolone acetate injection in the management of mild carpal tunnel syndrome

Abstract: Local glucocorticoid injection results in long-term improvement in nerve conduction parameters, symptom severity and functional scores in patients with mild CTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 22 publications
2
29
0
2
Order By: Relevance
“…Surgical treatment is generally preferred in severe cases of CTS, whereas nonsurgical treatment is reserved for mild-to-moderate CTS. Several studies have shown that local corticosteroid application provides clinical improvement and could be a primary treatment option for CTS (20, 21). In our study, local corticosteroid injection therapy showed a moderate effect size at the 3-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment is generally preferred in severe cases of CTS, whereas nonsurgical treatment is reserved for mild-to-moderate CTS. Several studies have shown that local corticosteroid application provides clinical improvement and could be a primary treatment option for CTS (20, 21). In our study, local corticosteroid injection therapy showed a moderate effect size at the 3-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant weight loss in the first 3 months in patients who were enrolled in our study, which is consistent with data in the literature. Furthermore, in various methods for CTS treatment, optimal improvements were found in the first 3 months, both clinically and electrophysiologically, and after that the effectiveness of treatment gradually decreased [23, 24]. Lack of improvement in NCS values of patients after losing weight suggests that the association between CTS and obesity may not be solely explained by excess body weight.…”
Section: Discussionmentioning
confidence: 99%
“…9 Corticosteroid injection is one of the few nonsurgical treatments with proven short-term effectiveness in the treatment of carpal tunnel syndrome (CTS). 21 Agarwal et al 1 showed that local injection of 40 mg methylprednisolone acetate into the carpal tunnel in mild CTS significantly reduced the symptoms in 80% of patients for at least 16 months, and it normalized electrodiagnostic parameters in 50% of subjects by 12 months after the treatment. 18 Local corticosteroid injection can be as effective as decompression surgery in relieving the CTS symptoms up to 1 year after treatment.…”
mentioning
confidence: 99%